An adaptive low-power transmission scheme for on-chip networks - Worm, Frédéric; Ienne, Paolo; Thiran, Patrick; De Micheli, Giovanni (Proceedings of the 15th International Symposium on System Synthesis, 2002)
Systems-on-Chip (SoC) are evolving toward complex heterogeneous multiprocessors made of many predesigned macrocells or subsystems with application-specific interconnections. Intra-chip interconnects are thus becoming one of the central elements of SoC design and pose conflicting goals in terms of low energy per transmitted bit, guaranteed signal integrity, and ease of design. This work introduces and shows first results on a novel interconnect system which uses low-swing signalling, error detection codes, and a retransmission scheme; it minimises the interconnect voltage swing and frequency subject to workload requirements and S/N conditions. Simulation results show that tangible savings in energy can be attained while achieving at the same time more robustness to large variations in actual workload, noise, and technology quality (all quantities easily mispredicted in very complex systems and advanced technologies). It can be argued that traditional worst-case correct-by-design paradigm will be less and less applicable in future multibillion transistor SoC and deep sub-micron technologies; this work represents a first example towards robust adaptive designs.